EKSTRAK DAUN SIRIH HIJAU DAN MERAH SEBAGAI ANTIOKSIDAN PADA MINYAK KELAPA - Hermiati, Rusli, Naomi Yemima Manalu, Mersi Suriani Sinaga (Universitas Sumatera Utara, 2013)
Extraction is the separation of a substance from the mixture, with the distribution of a solute between two solvents which can not be mixed to fetch solute from one solvent to another solvent. The purpose of this study was to determine the antioxidant activity found in betel leaf extract for coconut oil numbers peroxide analysis, antioxidant resistance, with Lovibond color test and to found variations in betel leaf types that produce the optimum operating conditions of antioxidants. In this study, green and red betel leaves extracted by using ethanol solvent, the extract is added to coconut oil and then tested peroxide number and color levels. The results obtained in this study were able to lower the number of betel leaves peroxide by 55.13% with the best optimum condition; volume of 150 ml of solvent, extraction time of 75 minutes, and stirring speed of 300 rpm for the raw material powder of red betel leaf.Keywords : extraction, antioxidants, peroxide number, betel, lovibond